Changes in conventional cardiovascular risk factors and the estimated 10-year risk of acute myocardial infarction or cerebral stroke in Sami and non-Sami populations in two population-based cross-sectional surveys: the SAMINOR Study. Issue 7 (19th July 2019) - Siri, Susanna Ragnhild Andersdatter; Eliassen, Bent Martin; Jacobsen, Bjarne K; Melhus, Marita; Broderstad, Ann Ragnhild; Michalsen, Vilde Lehne; Braaten, Tonje
Abstract : Objective: To describe changes in cardiovascular risk factors and in the estimated 10-year risk of acute myocardial infarction (AMI) or cerebral stroke (CS) between SAMINOR 1 (2003–2004) and SAMINOR 2 (2012–2014), and explore if these changes differed between Sami and non-Sami. Design: Two cross-sectional surveys. Setting: Inhabitants of rural Northern Norway. Participants: Participants were aged 40–79 years and participated in SAMINOR 1 (n=6417) and/or SAMINOR 2 (n=5956). Primary outcome measures: Generalised estimating equation regressions with an interaction term were used to estimate and compare changes in cardiovascular risk factors and 10-year risk of AMI or CS between the two surveys and by ethnicity. Results: Mean cholesterol declined by 0.50, 0.43 and 0.60 mmol/L in women, Sami men and non-Sami men, respectively (all p<0.001). Sami men had a small decline in mean high-density lipoprotein (HDL) cholesterol and an increase in mean triglycerides (both p<0.001), whereas non-Sami showed no change in these variables. Non-Sami women had an increase in mean HDL cholesterol (p<0.001) whereas Sami women had no change. Triglycerides did not change in non-Sami and Sami women. Systolic and diastolic blood pressure declined by 3.6 and 1.0 mm Hg in women, and 3.1 and 0.7 in men, respectively (all p<0.01). Mean waist circumference increased by 6.7 and 5.9 cm in women and men, respectively (both p<0.001). The odds of being a smoker declined by 35% in women and 46% in men (both p<0.001). Estimated 10-year risk of AMI or CS decreased in all strata of sex and ethnicity (p<0.001), however, Sami women had a smaller decline than non-Sami did. Conclusions: Independent of ethnicity, there was a decline in mean cholesterol, blood pressure, smoking, hypertension (women only) and 10-year risk of AMI or CS, but waist circumference increased. Relatively minor ethnic differences were found in changes of cardiovascular risk factors.